Stability of Bacillus thuringiensis (Bt-127) in different biopolymers against UV irradiation: Stability of Bacillus thuringiensis (Bt-127) in different biopolymers against UV irradiation - G V SURESHA; K S V P CHANDRIKA; P DURAIMURUGAN; S J RAHMAN; E BHARATHI (Journal of Oilseeds Research, 2023)
Microbial bioagents offer considerable promise for eco-friendly in insect pest management. Encapsulation using biopolymers is a safe and feasible technique that provides most protection for biopesticides. It improves their stability against UV radiation by coating the BT spores and crystals with biopolymers. The stability of the BT spore was observed in biopolymers compared to Bt- technical. Hence, the stability is good in (lingnosulphontae + BT + water, and chitosan + BT + water) formulations @ 5% and 0.1%respectively.